Experimental study of thin steel tubes welded by fiber laser - Bakosova, Dana; Bakosova, Alzbeta (Manufacturing Technology Journal, 2021)
The laser welding method is one of the youngest but the most progressive welding methods. The advantages of laser welding include: simple automation combined with modern computer technolo-gy, very low heat input to the weld, high productivity, high welding accuracy and low noise during laser operation. In this work, the sample meltings were prepared in a protective atmosphere varying the welding parameters - laser power, welding speed, or focus position. A total of 12 samples were prepared this way. The aim was to evaluate the shape and depth of the melting of the material for selected values of parameters. Based on this metallographic evaluation, the optimal welding parame-ters were selected for a pair of austenitic stainless steel tubes (X2CrNi19-11 and X5CrNiMo17-12-2) for fiber laser welding. Macrostructure and microstructure evaluations, microhardness tests and tensile tests were performed on these welded samples.
Keywords: steel; fiber laser; microhardness; weld; metallography